Spinocerebellar ataxia type 10 in the South of Brazil: The Amerindian-Belgian connection Ataxia espinocerebelar tipo 10 no sul do Brasil: A conexão Ameríndia-Belga - Teive H.A.G. (2015)
© 2015, Associacao Arquivos de Neuro-Psiquiatria. All rights reserved.Spinocerebellar ataxia type 10 (SCA10) is a rare form of autosomal dominant ataxia found predominantly in patients from Latin America with Amerindian ancestry. The authors report the history of SCA10 families from the south of Brazil (the states of Paraná and Santa Catarina), emphasizing the Belgian-Amerindian connection.